2009
DOI: 10.1161/strokeaha.108.526376
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PTEN Promoter Methylation in Cerebral Cavernous Malformations

Abstract: Background and Purpose-Cerebral cavernous malformations (CCMs) are prevalent cerebral vascular lesions involving aberrant angiogenesis. However, the underlying mechanism is poorly understood. Phosphatase and tension homolog deleted on chromosome 10 (PTEN), a tumor suppressor, is frequently deficient in various pathologies due to mutation or epigenetic alterations. PTEN promoter hypermethylation is a major epigenetic silencing mechanism leading to activation of angiogenesis in tumors. The present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…1,17 Recent findings that frequent epigenetic alteration in phosphatase and tensin homolog promoter led to deficiency of this protein expression in the ECs of familial CCMs may support this notion. 30,31 Furthermore, we (unpublished data, 2010) and others 2,29 have found that ECs derived from CCMs (CCM-ECs) exhibit unique angiogenesis properties, indicating a pathological background of CCM-ECs. Clinically, a different intracranial hemorrhage rate has been observed in CCMs carrying individual CCM gene mutations.…”
mentioning
confidence: 82%
“…1,17 Recent findings that frequent epigenetic alteration in phosphatase and tensin homolog promoter led to deficiency of this protein expression in the ECs of familial CCMs may support this notion. 30,31 Furthermore, we (unpublished data, 2010) and others 2,29 have found that ECs derived from CCMs (CCM-ECs) exhibit unique angiogenesis properties, indicating a pathological background of CCM-ECs. Clinically, a different intracranial hemorrhage rate has been observed in CCMs carrying individual CCM gene mutations.…”
mentioning
confidence: 82%
“…Total protein extraction and the electrophoresis were performed as described previously [33]. The blots were incubated at 4°C overnight with the following first antibodies: DLL4, p-Erk1/2, p-Akt and GAPDH (each 1:1000 dilution, Cell Signaling, Frankfurt am Main, Germany); Notch4 [1:200, specifically detect the cleaved domain (active form) of the protein, Santa-Cruz Technology, Heidelberg, Germany], VEGF (1:1000; Abcam, Cambridge, UK), Hey1 (1:200, Abcam), CCM3 (1:400; Atlas Antibodies, Stockholm, Sweden) and actin (1:1000; Sigma-Aldrich, Seelze, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Methylation specific PCR (MSP) was performed at four independent CpG sites within the PTEN promoter previously shown to be prone to methylation in CRC (ST-3) [33, 3941], using ZymoTaq Premix (Zymo Research) [42]. Reactions were carried out on a Peltier thermocycler in a 25 µL volume consisting of 12.5 µL of ZymoTaq premix solution, 2 µL each of 10 µM forward and reverse primers, 2 µL of bisulfite treated DNA template with approximately 25ng of DNA and 6.5 µL of DNAse, RNAse free water.…”
Section: Methodsmentioning
confidence: 99%